Acylated iridoid glucosides from Pseudocaryopteris paniculata (C.B.Clarke) P.D.Cantino. (January 2021) - Xu, Hong-Tao; Chen, Yi; Zhang, Cheng-Gang; Ju, Zheng-Cai; Wang, Yong-Li; Chou, Gui-Xin
Abstract: Phytochemical investigation of the ethyl acetate fraction of Pseudocaryopteris paniculata C.B.Clarke P.D.Cantino resulted in the identification of 26 undescribed iridoid glucosides (paniculosides A–Z), along with 7 known iridoid glucosides. Their structures were elucidated via two-dimensional nuclear-magnetic-resonance (2D-NMR) spectroscopy, high-resolution electrospray ionization mass spectroscopy (HR-ESI-MS), and chemical-hydrolysis methods. All isolated substances were analyzed for their cytoprotective effects against t -BHP-induced toxicity in HepG2 cells. Among the tested compounds, paniculoside A, paniculoside I, paniculoside T, and paniculoside U exhibited moderate cytoprotective activities with IC50 values in the range of 11.72–34.22 μM against t -BHP-induced toxicity. Graphical abstract: Image 1 Highlights: Thirty-three iridoid glucosides were isolated from Pseudocaryopteris paniculata C.B.Clarke P.D.Cantino. Twenty-six undescribed iridoid glucosides were reported. Four compounds exhibited moderate cytoprotective effects.